Minimization of torque ripples with optimized controller based four quadrant operation & control of BLDC motor. (October 2022) - V, Bharanigha; Mohamed Shuaib, Y.
Highlights: BLDC motors are widely utilized because of their qualities such as compact size, longer lifespan, and improved efficiency. BLDC motor available in a wide range of applications including aircraft, automation, computers, military, domestic appliances, and traction. Optimal benefit parameters are required to lessen torque ripples and regulate the speed of the BLDC motor by utilizing the APID controller. The hybrid method is the combination of the HHO and BWO based Luo converter. The optimization algorithms inspired by the nature of HHO and BWO are resolved to discover the problem in the work. Abstract: BLDC motors are widely utilized because of their qualities such as compact size, longer lifespan, and improved efficiency. In addition, BLDC motor available in a wide range of applications including aircraft, automation, computers, military, domestic appliances, and traction. These motors require an effective control method and also the controlling a BLDC motor in four quadrants are critical. Hence, An APID controller aimed at the speed regulation of the BLDC motor using multiple functions has been proposed in this paper. The curiosity of the proposed strategy is that it gives improved capacity, decreases improper irregular generation and can potential to change difficult optimization issues. Optimal benefit parameters are required to lessen torque ripples and regulate the speed of the BLDC motor by utilizing the APID controller. The hybrid method is the combination of the HHO and BWO based Luo converter. The proposed technique is straightforward in structure and heartiness to limit the issues of scientific figuring's. At the beginning, the optimization algorithms inspired by the nature of HHO and BWO are resolved to discover the problem in the work. Furthermore, the proficient hybrid HHO-BWO technique, which turns into the integrated strategy for the effective methodology, is executed to control the error values to provide the best optimal gain values. Here the control system, torque ripples have been diminished by regulating speed. EMF, stator current, torque, and speed are estimated based on the proposed regulation technique. The exhibition of the proposed system is implemented in the MATLAB/Simulink platform and compares with existing techniques such as HHO and BWO with APID control techniques.